2006
DOI: 10.1021/jf0618022
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate Induces Defense Responses in Grapevine and Triggers Protection against Erysiphe necator

Abstract: Grapevine is subject to a number of diseases that affect yield and wine quality. To limit the excessive use of phytochemicals in the vineyard, alternative strategies have to be developed. Plant treatment with signaling molecules like elicitors stimulates their natural defense mechanisms. To improve grapevine tolerance against fungal pathogens, Vitis vinifera plants were treated with a natural exogenous elicitor, methyl jasmonate (MeJA). MeJA-treated leaves (Cabernet Sauvignon foliar cuttings) reacted by increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 54 publications
4
93
0
4
Order By: Relevance
“…Along the same line, MeJA was also shown to promote expression of defense-related genes in grapes (Belhadj et al, 2006). Grapevines attacked by fungal pathogens usually result in reduced production and quality of wine.…”
Section: Jasmonates As Molecular Coordinators Capable Of Orchestratinmentioning
confidence: 91%
See 1 more Smart Citation
“…Along the same line, MeJA was also shown to promote expression of defense-related genes in grapes (Belhadj et al, 2006). Grapevines attacked by fungal pathogens usually result in reduced production and quality of wine.…”
Section: Jasmonates As Molecular Coordinators Capable Of Orchestratinmentioning
confidence: 91%
“…A capability of promoting resistance against pathogen attack was confirmed by increased tolerance towards the fungal pathogen Erysiphe necator (powdery mildew) after treatment with MeJA. Thus, it was demonstrated that treatment with MeJA is an alternative strategy for stimulating natural defense mechanisms in V. vinifera, reducing the need for fungicides against powdery mildew (Belhadj et al, 2006).…”
Section: Jasmonates As Molecular Coordinators Capable Of Orchestratinmentioning
confidence: 99%
“…Similarly, our results demonstrate that MYB14 and MYB15 are differentially expressed in response to various biotic and abiotic stresses (Figure 2), which mirrors the STS subgroup-specific expression, indicating the specificity of the interaction of the two TFs (MYB14 or MYB15) with certain STS genes. The observed differences in expression patterns of MYB14 and MYB15 also raises the question as to whether their own transcription is regulated by different upstream stress response pathways, such as the jasmonic-acid and ethylene-signaling pathways (Belhadj et al, 2006(Belhadj et al, , 2008a(Belhadj et al, , 2008bVezzulli et al, 2007).…”
Section: Myb14 and Myb15 Contain A C-terminal Aminomentioning
confidence: 99%
“…Pryce, 1977), methyl jasmonate elicitation (Belhadj et al, 2006;Jeandet et al, 2014b) and ozone treatment (Zinser et al, 2000). However, UV-C irradiation is mostly absorbed by the atmosphere and is scarcely received by field-grown plants.…”
Section: Effects Of Ultraviolet C On Stilbene Biosynthesismentioning
confidence: 99%